1984
DOI: 10.1007/bf01952573
|View full text |Cite
|
Sign up to set email alerts
|

Pineal indols and testosterone affect exploratory activity of male rats

Abstract: The testosterone level has an inverse relation to activity in the open-field test. This is more important in red light than in white light. Pineal indols do not disturb this action. Some of these results are consistent with the assumption that androgens play a role on the exploratory activity of adult subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…One study showed that T administration to male rats did not affect open field activity (Bitran et al, 1993), whereas other studies showed that T concentrations were inversely related to activity in the open field, with higher T levels associated with less activity (Lambadjieva, 1998;Rodriguez, Sosa, Hernandez, & Mas, 1984). The rats in the present study received a sustained amount of T from the implants, which produced supraphysiological concentrations of androgens and may have been sufficient to produce modest changes in motor behavior.…”
Section: Discussionmentioning
confidence: 52%
“…One study showed that T administration to male rats did not affect open field activity (Bitran et al, 1993), whereas other studies showed that T concentrations were inversely related to activity in the open field, with higher T levels associated with less activity (Lambadjieva, 1998;Rodriguez, Sosa, Hernandez, & Mas, 1984). The rats in the present study received a sustained amount of T from the implants, which produced supraphysiological concentrations of androgens and may have been sufficient to produce modest changes in motor behavior.…”
Section: Discussionmentioning
confidence: 52%
“…Melatonin, a pineal secretory product, reportedly plays a role in the modulation of arterial blood pressure [1–4], locomotion [5, 6], and body temperature [7, 8]. For example, systemic administration of melatonin induces arterial hypotension, hypo‐locomotion and hypothermia in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin, which is synthesized in the pineal gland, may play an important role in modulation of locomotor activity [Data and King, 1980;Rodriguez et a]., 19841. Systemic or intracerebral administration of melatonin to animals decreased spontaneous locomotor activity [Kovacs et al, 1974;Golus and King, 1981;Sugden 1983; Gaffori and Van Ree, 19851.…”
Section: Introductionmentioning
confidence: 99%